Microbial Life History Mediates the Drought‐Induced Decrease in Wood Decomposition in Subtropical Forests - Shuxian Jia; Xuhui Zhou; Yuling Fu; Guiyao Zhou; Lingyan Zhou; Xinxin Wang; Zheng Jiang; Jordi Sardans; Josep Penuelas (Ecology Letters, 2025)
Progressive intensification of drought regimes worldwide threatens wood decomposition ‐ a critical biogeochemical process in forest carbon cycling. However, the interactions between microbial strategies, wood traits and microclimate in regulating wood decomposition remain poorly understood under drought conditions. In a throughfall exclusion experiment (control 35% and 70% rainfall reduction) across 12 tree species, we found that drought‐induced reductions in wood CO 2 efflux rates were primarily driven by wood traits (density and carbon reduction) and shifts in fungal K / r ‐strategies. Coarse wood debris with higher Basidiomycota and lower Ascomycota abundance decomposed faster. Significant positive correlations were observed between fungal K / r ‐strategies and wood CO 2 efflux under control, 35%, and 70% rainfall reduction, while bacterial strategies showed no correlation. Our findings highlight the greater drought sensitivity of fungi than bacteria, emphasising their critical role in forest carbon dynamics and informing carbon models to improve the prediction of climate‐biosphere feedback in the changing world.